Original paper Estimation of testis volume in patients with varicocele treated by laparoscopic operation - Jabłonowski, Zbigniew; Miękoś, Eugeniusz; Różański, Waldemar (Archives of Medical Science, 2005)
Introduction: Seminal cord varices cause degenerative processes in testicles described as “orchidopathia e varicocele”. One of the coefficients of surgical treatment efficacy could be an increase of the testicle volume after surgical procedure. Material and methods: In 83 patients operated due to left side seminal cord varices the ultrasound examination of scrotum was performed aiming, among others, at the evaluation of both testicles volume. The examination was performed before the surgical procedure and then in the period of 6-8 months after the laparoscopically performed surgical procedure. The ultrasound examination was made by means of sector head (frequency of 7.5 MHz) and the examination unit B&K Medical 3535. During the examination the patient was in standing position. The testicle volume (in cm 3 ) was calculated by means of urological measurement module, which was the part of ultrasound examination unit software. Results: In the patients with seminal cord varices a statistically significant increase of the left testicle volume after applied laparoscopical surgery treatment was gained (p<0.001). The increase of the left testicle volume was found in 71 of 83 operated patients. Conclusions: 1. The application of the laparoscopic method in the patients with left seminal cord varices causes an increase of the testicle volume on the operated side. 2. The ultrasound evaluation of the testicle volume is safe for the patient and simple for the physician diagnostic method.